LGI 1 Antibody Encephaltis:Clinical characteristics and short term outcome along with review of literature. - Panicker, Praveen; Ramachandran, Dileep; Chandran, Raj Satheesh; Iype, Thomas (Nepal Journal of Neuroscience, 2024)
LGI1 (Leucine-rich glioma inactivated protein-1) antibody disease is one of the major causes of limbic encephalitis encountered in clinical practice manifesting with clinical seizures, behavioural disturbances and movement disorders. Here we discuss the varied presentations of this disease through three cases encountered at our center emphasizing the cardinal clinical, imaging and laboratory diagnostic features. Recognition of these characteristics would lead to early diagnosis and prompt management of this eminently treatable condition.